Peroxisome Proliferator Activated Receptor-α Association With Silent Information Regulator 1 Suppresses Cardiac Fatty Acid Metabolism in the Failing Heart. (November 2015) - Oka, Shin-ichi; Zhai, Peiyong; Yamamoto, Takanobu; Ikeda, Yoshiyuki; Byun, Jaemin; Hsu, Chiao-Po; Sadoshima, Junichi
Abstract : Background—: Heart failure is accompanied by changes in cardiac metabolism characterized by reduced fatty acid (FA) utilization. However, the underlying mechanism and its causative involvement in the progression of heart failure are poorly understood. The peroxisome proliferator activated receptor-α (PPARα)/retinoid X receptor (RXR) heterodimer promotes transcription of genes involved in FA metabolism through binding to the PPAR response element, called direct repeat 1 (DR1). Silent information regulator 1 (Sirt1) is a histone deacetylase, which interacts with PPARα. Methods and Results—: To investigate the role of PPARα in the impaired FA utilization observed during heart failure, genetically altered mice were subjected to pressure overload. The DNA binding of PPARα, RXRα, and Sirt1 to DR1 was evaluated with oligonucleotide pull-down and chromatin immunoprecipitation assays. Although the binding of PPARα to DR1 was enhanced in response to pressure overload, that of RXRα was attenuated. Sirt1 competes with RXRα to dimerize with PPARα, thereby suppressing FA utilization in the failing heart. DR1 sequence analysis indicated that the typical DR1 sequence favors PPARα/RXRα heterodimerization, whereas the switch from RXRα to Sirt1 takes place on degenerate DR1s. Sirt1 bound to PPARα through a region homologous to the PPARα binding domain in RXRα. A short peptide corresponding to the RXRα domain not only inhibited the interaction between PPARα and Sirt1 but also improved FA metabolism and ameliorated cardiac dysfunction. Conclusions—: A change in the heterodimeric partner of PPARα from RXRα to Sirt1 is responsible for the impaired FA metabolism and cardiac dysfunction in the failing heart. Abstract : Supplemental Digital Content is available in the text.